Time and Memory: The Report of Truth and Justice. The Case of Guatemala - Angulo Brenes, Sonia (2019)
The article analyzes the nature of the Truth and Justice Commissions, the case of Guatemala particularly. Two questions guide the research: Are these reports expressions of the memory? What is the function in order to past recovery? It is taken as starting point both, the understanding of the emergence of such Commissions, as well as their reports with the purpose of contextualizing their mainly elements. The focus is set out to the  report “Guatemala Memory of Silence”, came of the “Commission for Historical Clarification of the violations against human rights and the violent facts” based on the Oslo Accord (1994). It is concluded that Guatemalan report is a memory expression because it emerges in a transition context where this kind of resource was necessary, however its constant research of objectivity and neutrality does not allow the criticism possibility of past recovery.